2014
DOI: 10.1200/jco.2014.32.26_suppl.7
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of contrast enhanced spectral mammography (CESM) to breast MRI in breast cancer detection: An initial study for sensitivity analysis.

Abstract: 7 Background: CESM is a new study using contrast and dual energy digital mammographic technology to detect contrast enhanced cancer that may be invisible on conventional mammogram. Limited studies have shown that adding CESM to diagnostic workup adjunct with mammogram and breast ultrasound does increase sensitivity for breast cancer detection. More studies are needed to compare the sensitivity of CESM to BMRI to further define the role of CESM in breast cancer diagnosis. Methods: This study involved 50 malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, MRI is cost effective as a supplemental screening tool only for women with a >20% life-time risk of getting breast cancer, such as women with BRCA1 or BRCA2 mutations (11,12). Initial investigations done by other authors have shown that CEDM has significantly higher sensitivity and negative predictive value than 2D mammography and comparable to MRI (8,13,14). Hence, CEDM may be a suitable low-cost alternative in women with dense breasts or among those having higher than average life-time risk of breast cancer especially when MRI is not available or it cannot be performed (Figs.…”
Section: Main Pointsmentioning
confidence: 99%
“…However, MRI is cost effective as a supplemental screening tool only for women with a >20% life-time risk of getting breast cancer, such as women with BRCA1 or BRCA2 mutations (11,12). Initial investigations done by other authors have shown that CEDM has significantly higher sensitivity and negative predictive value than 2D mammography and comparable to MRI (8,13,14). Hence, CEDM may be a suitable low-cost alternative in women with dense breasts or among those having higher than average life-time risk of breast cancer especially when MRI is not available or it cannot be performed (Figs.…”
Section: Main Pointsmentioning
confidence: 99%